Effects of deliberate practice and self-efficacy on clinical skills performance in a fundamental nursing course - Erik Kusuma; Syaifuddin Kurnianto; Eko Prasetya Widianto; Mareta Deka Paraswati; Suhendra Agung Wibowo (KHD-Production, 2026)
Clinical skill deficits among vocational nursing students compromise patient safety, particularly when conventional training lacks structured feedback mechanisms. This study investigated the effects of a deliberate practice intervention and self-efficacy on clinical skills performance. A quasi-experimental pretest–posttest control-group design was conducted with 60 second-semester diploma nursing students, who were allocated via matched sampling to the experimental (n=30) or control (n=30) groups. The experimental cohort completed an eight-session deliberate practice program (90 minutes per week for four weeks), while the control group received standard instruction. Blinded assessors evaluated psychomotor skills using a validated Objective Structured Clinical Examination checklist, and self-efficacy was measured with the General Self-Efficacy Scale. Intervention fidelity was rigorously maintained through protocol checklists. The experimental group demonstrated significantly superior post-intervention clinical skills scores compared to controls (mean difference = 12.47, 95% CI [8.40, 15.60], p < .001). Self-efficacy independently predicted skill performance (β = 0.29, p = .008). Combined, the intervention and self-efficacy explained 58.3% of the variance in clinical performance (adjusted R² = 0.55, p < .001). Structured deliberate practice substantially enhances clinical competency in vocational nursing students, with self-efficacy functioning as a critical complementary predictor. Nursing educators should systematically integrate deliberate practice frameworks with targeted confidence-building strategies to optimize psychomotor skill acquisition and strengthen patient safety outcomes.